RUMAH SUSUN , SOLUSI KEBUTUHAN PERUMAHAN DAN PERBAIKAN LINGKUNGAN DI KOTA JAKARTA - Susy Irma Adisurya (Universitas Trisakti, 2010)
AbstractLiving in a flat becomes a new phenomenon that interest urban people nowdays. The Flat Development Program is intending to create the better environment, including solving the people density problems, housing fulfilment for urban communities , and expanding urban green space in big cities, especially in Jakarta.This reseach is using qualitative method . It shows that the development of vertical housing such as flats are carrying some goodness to the city nevironment, including (1) the effecienci and optimalization of space that produce green environment and (2) the centered density is a certain space Abstrak Tinggal di rumh susun sudah menjadi suatu fenomena baru yang diminati oleh masyarakat perkotaan. Program Pembangunan Rumah Susun (Rusun) yang diharpkan akan membawa perbaikan lingkungan, di anataranya menyelesaikan masalah kepadatan penduduk, pemenuhan perumahan rakyat di kota besar dan pengembangan ruang hijai khususnya Jakarta.Penelitian ii menggunakan metode kulaitatif. Hasilnya menunjukkan bahwa pembangunan vertical housing berupa rumah Sususn ini membawa beberapa manfaat pada lingkungan kota seperti (1)Efisiensi dan optimalisasi lahan, hingga tercipta suasanan ramah lingkungan ( 2) Pemusatan kepadatan pada suu kawasan